BUDAYA BELAJAR DIKELAS V SD MUHAMMADIYAH MRISI - Dwi Erawati Susanto; Enung Hasanah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research aims to find cultural activities of learning in Muhammadiyah Mrisi Elementary School Class V. In this study using qualitative methods. Data collection in the form of observations and interviews. The instrument of this study is the researcher himself as the data collector described and analyzed. Data analyzed by reduced is irrelevant presentation of data and conclusions are drawn. The results in this study showed that students' learning cultures are very diverse including in the creation of study schedules, literacy, noting repeat reading subjects that have been taught. Therefore it can be concluded that the culture of learning has a positive effect on student intelligence. There is a culture of learning of course there is a culture of success with thought and skills.